The Question about the scientific position of transformative pedagogy - Novak, Bogomir (Šolsko polje, 2012)
The aim of this paper is to answer the question about the scientific position of transformative pedagogy and school. Th e aim is also to look into how the dimensions of transformative pedagogy can be judged according to the new epistemological criteria in comparison with the transmissive school. Transformative pedagogy is an alternative type of reform pedagogy and part of the new holistic paradigm. The differences between transmissive and transformative schools are presented in a special table. The existent Cartesian Newtonian anthropocentric Enlightenment paradigm conceptually no longer suffices for the solution of complex world issues. Scientific progress has resulted in the change of epistemological criteria for what is considered scientific. In this paper, the characteristics of postanthropocentric pedagogy and epistemology are explained. Modern pedagogy is characterized by understanding, dialogue, multiculturalism, students' individuality and their orientation towards learning vis-a-vis the previous school of knowledge transmission, rational argumentation and the priority of teaching. This paper points out which epistemological issues arise from the confrontation of the Cartesian and the new post-anthropocentric holistic paradigms as frames for two different pedagogies.
Keywords: learning; učenje; konstruktivizem; constructivism; transformative school; transformativna šola; epistemologija; epistemology; paradigm; paradigma; education; vzgoja in izobraževanje